The Service Sector in Poland as the Affecting Factor to the Growth in the Economy - Kisiel, Roman; Wiśniewska, Dagmara (Olsztyn Economic Journal, 2016)
The aim of the article was to determine service sector's influence on the economic growth in Poland. The article describes various factors influencing the development of the third sector and its influence on economic processes. The consumer behaviours of clients - their expectations in relation to the service market, have been presented. The characterization was carried out based on secondary data and studies carried out by the authors. Based on the carried out research, it can be stated that 75% of service providers indicate difficulties when setting up a service-oriented business. The existing service-oriented entities are of sufficient demand as confirmed by the 37% of service providers, which translates to direct satisfaction from the work of 62% of businesses. Characterized by the highest demand are medical, hairdressing and cosmetic services. It was also proven that the positive influence of services on the general condition of the economy has a direct effect on the increase in average employment over a long period of time. Customers decide to employ the services of the private sector more frequently as they believe the quality of the services provided by the public sector to be lower. On the whole, they rate the quality of services in Poland as average. Among the analysed groups of respondents 60% believe that Poland's accession to the EU had a significant influence on the quality, variety and availability of services.